The Use of Oral Antidiabetic Drugs in Type-2 Diabetes Mellitus Patients with Macrovascular and Microvascular Complications at an Indonesian Tertiary Hospital, July-September 2023 - Rasagama Putra Soesanta; Sri Purwaningsih; Hermawan Susanto; Klára Bodova (Universitas Airlangga, 2026)
Introduction: The incidence of Type 2 Diabetes Mellitus (T2DM) in Indonesia remains high and can lead to both macrovascular and microvascular complications, making research on the use of T2DM medications and their complications an important area of study. This study examines the use of oral antidiabetic drugs in T2DM patients with macrovascular and microvascular complications at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: A descriptive, retrospective study was conducted using total sampling of medical records with the inclusion criteria of this study being 162 patients who were treated in the Internal Medicine Outpatient at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, for the period of July–September 2023 with the diagnosis code ICD-10 E11 and were treated with oral antidiabetic drugs. The exclusion criteria of this study were patients who are using insulin as their primary therapy. Results: Out of 162 patients, the demographic distribution showed that most patients were female (51.23%), with the highest age group being 55-64 years (41.35%). Body Mass Index (BMI) was mostly in the 18.5-22.9 and 23-24.9 ranges (33.95%), and the majority had been living with DM for 6-10 years (44.44%). Monotherapy, primarily metformin, was commonly used across all microvascular (retinopathy, nephropathy, neuropathy) and macrovascular (stroke, coronary heart disease (CHD), peripheral artery disease (PAD)) complications. The most frequently used combination therapy was metformin + glimepiride. Conclusion: The use of metformin as monotherapy and the combination of metformin and glimepiride were the most commonly used treatments for T2DM patients with complications.